Rapid Prototyping Implementation in the Catholic University of Pereira (2020)
This article sets out the background, strategies and implementation of rapid prototyping technology through investigation training experiences with the seedlings in “technology and design” line of Industrial Design program, by strengthening project processes for academic programs from the Catholic University of Pereira. Process that leads to the understanding, analysis and production of prototypes and models according to the context and the present needs, in an interdisciplinary way.